Sulphatation Does Not Appear to Be a Protective Mechanism to Prevent Oxysterol Accumulation in Humans and Mice - Acimovic, Jure (Public Library of Science, 2013)
24S- and 27-hydroxycholesterol (24OHC and 27OHC) are potent regulators of different biochemical systems in vitro and are the major circulating oxysterols. A small fraction of these oxysterols has been reported to be sulphated but there are no detailed studies. We considered the possibility that sulphatation is a protective mechanism preventing accumulation of free oxysterols. Using an accurate assay we found the sulphated fraction of 24OHC and 27OHC in circulation of adults to be less than 15% of total. In two patients with a mutation in CYP7B1 and markedly increased levels of 27OHC the sulphated fraction was 8% and 10% respectively. Infants with severe neonatal cholestasis had however markedly increased sulphate fraction of the above oxysterols. In untreated mice the degree of sulphatation of 24OHC and 27OHC in serum varied between 0 and 16%. Similar degree of sulphatation was found in two mouse models with markedly increased levels of 27OHC and 24OHC respectively. Bile duct ligated mice had higher levels of oxysterols than sham-operated controls but the sulphate fraction was not increased. We conclude that a primary increase in the levels of the oxysterols due to increased synthesis or reduced metabolism in adults and mice does not induce increased sulphatation.